Astrocytes orchestrate neuroprotection and pathogenesis via bidirectional neuronal interactions in Parkinson’s disease - Yifan Li; Qiang Li; Yemin Wang; Xuejing Wang; Guangfu Di; Meng Niu; Zhiliang Xu; Yanjiao Huang (Journal of Physiology and Biochemistry, 2026)

Silicon-mediated mitigation of cadmium risk in peanut-growing soil depends on cultivar-specific defense strategies - Nengde Zeng; Guowei Cao; Mingda Liu; Yuan Hu; Yaojing Wang; Mengyuan Ni; Na He; Wanting Ling; Hongtao Zou; Dan Yang (Applied Soil Ecology, 2026)

Decoupling transport and reactions in reactive transport simulations - Jordi Petchamé-Guerrero; Jesus Carrera; Jingjing Wang; Chunmiao Zheng (Advances in Water Resources, 2026)

Go north: Isotope and aDNA analysis reconstructing the life history of a first-generation immigrant in the early Western Zhou Yan state - Xinyi Ouyang; Nina An; Jing Wang; Chen Duan; Yingliang Yang; YiHsien Lin; Chao Ning; Jingning Guo; Xiaohong Wu (Archaeological and Anthropological Sciences, 2026)

High-Purity Narrow-Band Green Light KAl11O17: Eu2+, Mn2+ Phosphor Prepared Based on Energy Transfer Effect - Zhihui Wang; Xiaohua Wang; Yumeng Jia; Jing Wang; Zhongxiang Shi; Qingyun Yan (Journal of Fluorescence, 2026)

Atmospheric Blocking Pattern as the Primary Driver of Subseasonal Greenland Ice Sheet Summer Melt Variability - Ruiwei Guo; Yao Yao; Dehai Luo; Jiaqi Shi; Lijuan Hua; Ruonan Zhang; Hejing Wang (International Journal of Climatology, 2026)
The anomalous summer melting of the Greenland Ice Sheet (GrIS) is one of the key signals of ongoing climate system changes. The complex spatiotemporal characteristics of GrIS and its impacts on global sea‐level rise have attracted increasing attention. Although previous studies have suggested that atmospheric blocking circulation can drive extreme melting events, the quantitative influence of subseasonal‐scale atmospheric processes on the total summer melt remains poorly understood. Based on a scale‐separation approach combined with Modèle Atmosphérique Regionale (MAR) simulations and satellite observations, this study provides the first systematic quantitative assessment of the contribution of subseasonal circulation processes to summer melting of the GrIS. While subseasonal processes account for an average of ~20% of the total summer melt, we find that a single pattern—Greenland Blocking (GB)—dominates this contribution. GB alone is responsible for up to 47% of the subseasonal melt, equating to approximately 10% of the total summer melt. The remaining subseasonal variance is driven by a spectrum of other circulation modes. To unravel the remaining subseasonal signal, we employ K‐means clustering to identify four distinct non‐blocking circulation patterns. However, their individual contributions are substantially smaller than that of GB. This study reframes the understanding of summer GrIS melt by highlighting the overwhelming dominance of blocking within the subseasonal framework.

Cross-population structural variation landscape of the Zhikong scallop (Chlamys farreri) reveals the genetic architecture of molluscan growth - Kuo Ni; Danyang Wang; Mingyi Sui; Shiyi Li; Xiaomei Chen; Yalin Guan; Jing Wang; Shi Wang; Xiaoting Huang; Lisui Bao (Aquaculture, 2026)

Development of a rapid and visual detection platform for Aeromonas salmonicida based on the RPA-CRISPR/Cas12a system - Fusheng Tan; Ran Zhao; Jing Wang; Di Wang; Shaowu Li (Aquaculture, 2026)

Combined application of organic amendments improved soil quality and maize yield in coastal saline soil - Xiaolong Bai; Ruixiao Dong; Shang Wang; Mengmeng Chen; Xiaobin Li; Jing Wang; Jie Zhou; Yuyi Li; Hongyuan Zhang; Gilles Colinet (Applied Soil Ecology, 2026)

Emerging Viruses in Decapod Crustaceans: A Global Review - Xuan Dong; Guohao Wang; Kejun Wang; Kaisong Zhang; Hua Xu; Liying Wang; Xuan Li; Liang Qiu; Win Surachetpong; Jing Wang; Jee Eun Han; Kathy F. J. Tang; et al. (Reviews in Aquaculture, 2026)
Due to its advantages of a short production cycle, wide market demand, and profitability, decapod crustacean aquaculture has become one of the fastest‐growing food production systems. However, disease outbreaks have become one of the most important factors limiting the sustainability of decapod crustaceans. This review synthesizes current advancements in the understanding of emerging viral pathogens in decapod crustacean aquaculture, with emphasis on their genomic‐based taxonomical classification, susceptible hosts, global distribution, clinical manifestations, pathogenic mechanisms, diagnostic developments, and management strategies. This paper summarizes details of emerging viruses with confirmed pathogenicity (such as decapod iridescent virus 1), as well as viruses with uncertain or yet‐unconfirmed pathogenic roles. In addition, we highlight the role of next‐generation sequencing in virus discovery and examine the challenges posed by coinfection with other microorganisms. This review provides information to help the decapod crustacean aquaculture industry in setting up early warning systems to prevent the introduction of emerging pathogens into the production systems.

Earthworms modulate soil microbiota to enhance straw degradation and enrich wheat-available nutrients - Zhengke Song; Ling Ling; Jiaxin Li; Yanan Sun; Yanfang Luo; Kun Zhang; Li Zhao; Lifeng Guo; Jinzhao Gu; Yuzun Wang; Wensheng Xiang; Junwei Zhao; et al. (Applied Soil Ecology, 2026)

Macro‐Hybrid and Micro‐Hybrid of Fish - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
This study reviews the progress in fish breeding, focusing on distant hybridization and gynogenesis, and introduces the theory of macro‐hybrid and micro‐hybrid. The macro‐hybrid refers to the allo‐progeny derived from distant hybridization, including the allo‐progenies. The micro‐hybrid refers to the auto‐progenies derived from distant hybridization or heterologous sperm‐induced gynogenesis, which possess a genome derived predominantly from the maternal but contain DNA fragments originating from the paternal. Macro‐hybrids induce significant phenotypic changes, while micro‐hybrids improve growth rate and stress resistance. Both hybridization and gynogenesis exhibit high selective pressure. This review elucidates how selective pressures (homozygosity + heterologous sperm + cold/heat shock) of the heterologous sperm‐induced gynogenesis contribute to the generation of effective genetic variations. The study also presents the technologies of macro‐hybrid and micro‐hybrid. In macro‐hybrids of distant hybridization, parental chromosome numbers are closely matched, enabling the formation of fertile allo‐diploid and allo‐tetraploid strains. In micro‐hybrid of distant hybridization, equal or differing chromosome numbers between parents yield fertile auto‐tetraploid and auto‐diploid strains. In micro‐hybrid of heterologous sperm‐induced gynogenesis, equal or different chromosome numbers between parents yield auto‐diploid strains. The integration of heterologous sperm‐induced gynogenesis, back‐cross, and self‐cross strategies can address the issue of all‐female progeny resulting from gynogenesis. A series of auxiliary breeding techniques is established to support the macro‐hybrid and micro‐hybrid breeding. Case studies of superior fish strains developed through macro‐hybrid and micro‐hybrid breeding are presented. The establishment of macro‐hybrid and micro‐hybrid theory and breeding technologies holds significant value for fish breeding.

Cover Image - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
The cover image is based on the article Macro‐Hybrid and Micro‐Hybrid of Fish by Shaojun Liu et al., https://doi.org/10.1111/raq.70106 . image

Subsurface organic ameliorant is beneficial in reducing inorganic carbon loss and improving carbon sequestration in saline soils - Ru Yu; Jiashen Song; Jie Zhou; Fangdi Chang; Xiaobin Li; Jing Wang; Haoruo Li; Xia Zhang; Hua Zhang; Yuexin Zhang; Hongyuan Zhang; Yuyi Li (Applied Soil Ecology, 2025)

Impacts of green manure rotations and alkaline amendments on soil health and assembly and function of bacterial communities - Jinchang Liang; Heli Shi; Bikun Xiang; Luping Chi; Rui Wang; Guangwei Sun; Yuxiao Sun; Jing Wang; Jun Tan; Xiaoqiang Wang (Applied Soil Ecology, 2025)

Different responses of ammonia-oxidizing bacteria and archaea to yak dung addition regulate nitrogen cycle in an alpine meadow - Xiaoyue Yin; Luming Ding; Tianyang Zhou; Yijing Wang; Changting Wang; Xinhua He (Applied Soil Ecology, 2025)

Successive organic fertilizer substitution alleviated net ecosystem carbon loss in new vegetable field converted from rice paddy - Quan Tang; Feiyi Zhang; Jing Wang; Wenxia Dai; Zhenwang Li; Weiqin Yin; Xiaoyuan Yan; Xiaozhi Wang (Applied Soil Ecology, 2025)

Divergent effects of biomass-derived carbon dots application and sweetpotato planting on accumulations of soil microbial necromass carbon in Vertisol - Jing Wang; Meng Zhu; Xiaoya Zhu; Qiangqiang Zhang; Yongchao Yu; Peng Zhao; Ming Liu; Rong Jin; Zhonghou Tang (Applied Soil Ecology, 2025)

Natural succession and artificial management have different effects on soil microbial ecological patterns in wetland resulting from land-use change - Yijing Wang; Guodong Zheng; Changchao Li; Yongkang Zhao; Junyu Dong; Zhiliang Wang; Guohong Lu; Zongcheng Chen; Zhoubin Dong; Kang Liu; Huaizhi Bo; Jian Liu (Applied Soil Ecology, 2025)

Tree mycorrhizal associations strongly mediate soil microbial β-diversity along an elevational gradient in a warm-temperate forest - Xinyue Wang; Yaru Wang; Yu Wang; Jieyan Yang; Hongyi He; Yuchen Ren; Chenlin Wang; Haibo Li; Xiongzhi Zhang; Huifang Zhang; Jingjing Wang; Xiuqing Yang; et al. (Applied Soil Ecology, 2025)

The Research Advances in Distant Hybridization and Gynogenesis in Fish - Qizhi Liu; Shi Wang; Chenchen Tang; Min Tao; Chun Zhang; Yi Zhou; Qinbo Qin; Kaikun Luo; Chang Wu; Fangzhou Hu; Yude Wang; Qingfeng Liu; et al. (Reviews in Aquaculture, 2025)
Distant hybridization and gynogenesis are two prevalent breeding techniques for fishes. Drawing from the research achievements of our team and the existing literature, we summarize the reproductive traits and genetic features of fishes derived from distant hybridizations and gynogenesis, and we deduce the fundamental mechanisms of these two methods and compare them, discerning their common and different characteristics. Both distant hybridization and gynogenesis techniques can alter genotypes and phenotypes, thus establishing them as significant breeding methods. Additionally, the genetic principles and the basic biological characteristics of distant hybridization and gynogenesis in fish have been inferred. We propose the concepts of macro‐hybrid and micro‐hybrid based on extensive experimental findings from fish distant hybridizations and gynogenesis. The term “macro‐hybrid” refers to offspring from distant hybridization that possess two distinct subgenomes, each inherited from one of the two parental species, such as allodiploid and allotetraploid lineages. The concept of “micro‐hybrid” refers to offspring, including autodiploid and autotetraploid lineages, as well as those resulting from artificial gynogenesis, whose genome almost originates solely from the maternal parent but in which certain DNA fragments derived from the paternal parent insert. Distant hybridization and gynogenesis are vital techniques in fish genetics, breeding, and evolution. We highlight the prospective paths for research and application of distant hybridization and gynogenesis in fishes.

Subsurface manure application enhances soil quality, ecosystem multifunctionality, and crop yield in the North China Plain - Haoruo Li; Yiwei Shang; Jiansheng Gao; Hongyuan Zhang; Haotian Chen; Xiquan Wang; Jianjun Guo; Xia Zhang; Jing Wang; Yuyi Li (Applied Soil Ecology, 2024)

Long-term stationary fertilization decreased soil health in field-grown sweetpotato by increasing soil-borne diseases or allelochemicals - Xiaoya Zhu; Peng Zhao; Jing Wang; Qiangqiang Zhang; Yongchao Yu; Ming Liu; Rong Jin; Zhonghou Tang (Applied Soil Ecology, 2024)

Tracking autumn photosynthetic phenology on Tibetan plateau grassland with the green–red vegetation index - Wangchao Li; Rui Chen; Dujuan Ma; Changjing Wang; Yajie Yang; Cong Wang; Huai Chen; Gaofei Yin (Agricultural and Forest Meteorology, 2023)

Correction of illumination effects on seasonal divergent NIRv photosynthetic phenology - Rui Chen; Gaofei Yin; Guoxiang Liu; Yajie Yang; Changjing Wang; Qiaoyun Xie; Wei Zhao; Aleixandre Verger (Agricultural and Forest Meteorology, 2023)

Early–maturing cultivar of winter wheat is more adaptable to elevated [CO2] and rising temperature in the eastern Loess Plateau - Yuanling Zhang; Shu Kee Lam; Ping Li; Yuzheng Zong; Dongsheng Zhang; Xinrui Shi; Xingyu Hao; Jing Wang (Agricultural and Forest Meteorology, 2023)